Factors Affecting the Quality of Diagnosis Coding and Medical Record at Dr. Moewardi Hospital, Surakarta - Warsi Maryati; Bhisma Murti; Dono Indarto (Journal of Health Policy and Management, 2016)
Background: Diagnosis coding is atool for identifying and grouping diseases, disorders, symptoms, and other disease-related outcomes, such as poisoning, adverse effect of drugs and chemicals, injury. Diagnosis code can be used in policy making and costing medical care. Doctors, nurses, coding personnel, and medical record quality, may affect the quality of diagnosis coding. This study aimed to investigate factors that affects the quality of diagnosis coding at Dr. Moewardi Hospital, Surakarta.Subjects and Method: This was an analytic observational using cross sectional design. This study was conducted at Dr. Moewardi Hospital, Surakarta, Indonesia. A total of 250 inpatient medical record document at Dr. Moewardi Hospital were selected for the study bystratified random sampling.The data was analyzed by structural equation modeling (SEM).Results:Sub-specialistic doctor (b = 1.13; 95%CI = 0.06 to 0.33; p = 0.039),civil servant doctor(b = 0.84; 95%CI = 0.06 to 1.62; p =0.034),nurse working ≥ 5 years (b = 1.77; 95% CI = 1.13 to 2.42; p<0.001), significantly increased the quality of medical record. Coding personnel aged ≥40 years (b= 1.70; 95%CI = 0.64 to 2.77; p = 0.002), coding personnelworking ≥5 years (b = 1.70; 95%CI= 0.98 to 2.42; p 0.001), and coding personnel has ≥ 5 times training(b = 2.62; 95% CI = 1.40 to 3.83; p <0.001), significantly increased the quality of diagnosis coding.Conclusion: Sub-specialistic doctor, civil servant doctor, nurse working ≥5 years, significantly increased the quality of medical record. Coding personnel aged ≥40 years, coding personnel working ≥5 years, and coding personnel has ≥ 5 times training, significantly increased the quality of diagnosis coding.Keywords: Quality of diagnosis coding, quality of medical record, doctor, nurse, coding personnel.Correspondence: Warsi Maryati. School of Medical Records and Health, APIKES Citra Medika, Surakarta. Email: warsi_maryati@yahoo.comJournal of Health Policy and Management (2016), 1(2): 61-70https://doi.org/10.26911/thejhpm.2016.01.02.01